Effect of Da-Cheng-Qi decoction for treatment of acute kidney injury in rats with severe acute pancreatitis - Ling Yuan; Lv Zhu; Yumei Zhang; Huan Chen; Hongxin Kang; Juan Li; Xianlin Zhao; Meihua Wan; Yifan Miao; Wenfu Tang (BMC, 2018)
Abstract Background The traditional Chinese formula Da-Cheng-Qi-decoction (DCQD) has been used to treat acute pancreatitis for decades. DCQD could ameliorate the disease severity and the complications of organ injuries, including those of the liver and lungs. However, the pharmacological effects in the kidney, a target organ, are still unclear. This study aimed to investigate the herbal tissue pharmacology of DCQD for acute kidney injury (AKI) in rats with severe acute pancreatitis (SAP). Methods Rats were randomly divided into the sham-operation group (SG), the model group (MG) and the low-, medium- and high-dose treatment groups (LDG, MDG, and HDG, respectively). Sodium taurocholate (3.5%) was retrogradely perfused into the biliopancreatic duct to establish the model of SAP in rats. Different doses of DCQD were administered to the treatment groups 2 h after the induction of SAP. The major components of DCQD in kidney tissues were detected by HPLC-MS/MS. Inflammatory mediators in the kidney tissues, as well as serum creatinine (Scr), blood urea nitrogen (BUN) and pathologic scores, were also evaluated. Results Ten components of DCQD were detected in the kidneys of the treatment groups, and their concentrations increased dose-dependently. Compared with the SG, the levels of inflammatory mediators, Scr, BUN and pathological scores in the MG were obviously increased (p < 0.05). The high dose of DCQD showed a maximal effect in downregulating the pro-inflammatory mediators interleukin-6 (IL)-6 and tumour necrosis factor-α (TNF-α), upregulating anti-inflammatory mediators IL-4 and IL-10 in the kidney and alleviating the pathological damages. DCQD decreased the pancreas and kidney pathological scores of rats with SAP, especially in the HDG (p < 0.05). Compared with the MG, the level of Scr in the HDG was significantly decreased (p < 0.05). Conclusions DCQD ameliorated AKI in rats with SAP via regulating the inflammatory response, which might be closely related to the distribution of its components in the kidney.